Growth Parameters, Economic Analysis and Blood Characteristics of Weaned Pigs Fed Cashew Reject Kernel Meal - Ojediran, Taiwo; Oyebamiji, Opeyemi; Areo, Evelyn; Emiola, Isiak (Polish Journal of Natural Sciences, 2021)
Growth parameters, economic analysis and blood characteristics of weaned pigs fed graded levels of cashew reject kernel meal (CRKM) were studied in a 42 day trial. Forty (40) weaned pigs with mean weight of 8.67±0.99 kg were randomly assigned into four experimental diets such that Diets 1, 2, 3 and 4 contained 0%, 5%, 10% and 15% CRKM respectively. The chemical profile of CRKM showed 21.10% crude protein, 35.09% ether extract, 9.20% moisture, 6.83% crude fibre, 4.10% ash, 23.67% nitrogen fee extract, 11.69 MJ/kg metabolizable energy, 0.01% tannin, 0.26% saponin, 0.19% phytate, and 19.22 μg/kg ppm aflatoxin. The results showed that feed intake, economic indices, haematological parameters, and serum metabolites like alanine aminotransferase, asparatate aminotransferase, albumin and glucose were significantly influenced (p < 0.05). Conclusively, incorporation of up to 15% CRKM in weaned pigs’ diet favour growth performance, lowered feed cost, improved economic advantages and was not deleterious to the haematological and serum metabolites.